Fiscal variables and bond spreads: evidence from eastern European countries and Turkey - Christiane Nickel; Philipp Rother; Jan C. Rülke (European Central Bank (ECB), 2009)
We investigate the impact of fiscal variables on bond yield spreads relative to US Treasury bonds in the Czech Republic, Hungary, Poland, Russia and Turkey from May 1998 to December 2007. To account for the importance of market expectations we use projected values for fiscal and macroeconomic variables generated from Consensus Economics Forecasts. Moreover, we compare results from panel regressions with those from country (seemingly unrelated regression) estimates, and conduct analogous regressions for a control group of Latin American countries. We find that the role of the individual explanatory variables, including the importance of fiscal variables, varies across countries.
Keywords: C33; E43; E62; H62; 330; Budget deficits; determination of interest rates; Eastern European countries; Fiscal Policy; Öffentliche Anleihe; Haushaltsdefizit; Finanzpolitik; Zins; Polen; Russland; Tschechien; Ungarn; Türkei